The Long-term Earnings Consequences of General vs. Specific Training of the Unemployed - Anders Stenberg; Olle Westerlund (Institute for the Study of Labor (IZA), 2014)
Training programs for the unemployed typically involve teaching specific skills in demand amongst employers. In 1997, Swedish unemployed could also choose general training at the upper secondary school level. Despite the dominance of programs offering specific training, long-term relative earnings effects of general vs. specific training are theoretically ambiguous. Analyzing detailed administrative data 1990-2010, we find specific training associated with higher earnings in the short run, but that earnings converge over time. Results also indicate that individuals act on their comparative advantages. Long-run earnings advantages of general training are found for females with limited prior education and among metropolitan residents.
Keywords: I21; J62; J68; 330; active labor market programs; adult education; vocational training